(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The experimental study is to examine the influence of the aspect ratio on the steel fiber reinforced geopolymer Concrete Geopolymer blends were prepared with fly ash and activated alkali solution (NaOH and Na2SiO3) 0.35 ash solution. Steel fiber hook machines with a ratio of 30, 60 and 90 with a volumetric fraction of 0.0%, 0.25%, 0.50%, 0.75% and 1.0% by weight of conventional geopolymer gecko. The size of the beam of 100 mm x 100 mm x 500 mm for flexural strength tests of all samples were cured for 28 days with a different percentage of fiber and it was found that reinforced concrete reinforced concrete greatly improved resistance. It has been found that the optimal fiber content compensates for the fraction of volume of 0.75% and the aspect ratio 90 for the flexural strength of the beam. It has also been observed that an increase in fiber content at an optimum value increases the strength of the concrete.